Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 20074 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Ashmeadiella Cockerell, 1897", "Geometry POLYGON((-136.40625 62.267922,-136.40625 3.513421,-42.1875 3.513421,-42.1875 62.267922,-136.40625 62.267922))" ] } The dataset includes 20074 records from 12 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0001142-160509122628363/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences